Investigation of pyrethroid resistance mutations in Linognathus stenopsis lice collected from goats in western and northwestern Iran - Seydi-Gazafi, Khadijeh; Tavassoli, Mousa; Mardani, Karim (Frontiers in Veterinary Science, 2024)
Linognathus stenopsis lice are an extensive parasitic concern in goat populations worldwide, posing significant economic and health risks. This study examined the identification of pyrethroid resistance alleles of resistance to pyrethroid and mutations in L. stenopsis samples obtained from goats in five provinces in western and northwestern Iran. Morphological and molecular techniques were employed to identify the louse species. Molecular identification methods and gene sequencing were used to identify resistance-associated mutations in the voltage-gated sodium channel (VGSC) gene. The results revealed that six amino acid substitutions, including threonineto-isoleucine (T917I), leucine-to-phenylalanine (L920F), isoleucine-to-phenylalanine (I927F), phenylalanine-to-alanine (F928A), valine-to-arginine (V929R), and arginine-to-leucine (R930L) mutations, were present in the VGSC gene of L. stenopsis lice from various regions of Iran. These findings suggest the potential for pyrethroid resistance development in this louse species, highlighting the importance of integrated pest management (IPM) strategies. Such strategies, which combine selective insecticides, regular grooming, and environmental sanitation, are crucial for effectively managing L. stenopsis infestations and preserving the efficacy of pyrethroids for pest control. Moreover, the emergence of novel kdr mutations underscores the need for ongoing research into the molecular mechanisms underlying these mutations. This research is vital for developing strategies to combat pyrethroid resistance and maintaining the efficacy of insecticides in controlling lice. These findings suggest the potential for pyrethroid resistance development in this louse species and emphasize the importance of integrated pest management (IPM) strategies that combine selective insecticides, regular grooming, and environmental sanitation to effectively manage L. stenopsis infestations and preserve the efficacy of pyrethroids for pest control.Furthermore, the emergence of novel kdr mutations necessitates ongoing research into the molecular mechanisms underlying these mutations to develop strategies to combat pyrethroid resistance and to maintain the efficacy of insecticides in controlling lice, which pose significant health risks to animals and humans.